Aggregated forms of heparin-binding and non-heparin-binding proteins of boar seminal plasma and their binding properties - Manásková, P; Mészárosová, A; Liberda, J; Voburka, Z; Tichá, M; Jonáková, V (Folia biologica, 1999)
Boar seminal plasma proteins were separated by affinity chromatography on immobilized heparin into two portions: heparin-binding (H+) and non-heparin-binding (H-) proteins. Gel chromatography of the H+ portion yielded four main protein fractions of >150, 45, 30 and 20 kDa, while that of the H- portion resulted in the separation into three main protein fractions of >150, 30 and 20 kDa. HPLC analysis and N-terminal sequencing used to characterize the composition of the protein fractions obtained by gel chromatography revealed that all consisted of low (12-16 kDa) molecular weight components: the H+ fraction consisted of DQH sperm protein, AQN and AWN spermadhesins whereas the H- fraction consisted of PSPI and PSPII spermadhesins. The high molecular weight values of fractions obtained by gel chromatography thus suggest that the proteins are present in boar seminal plasma in the form of aggregates. Interactions of individual boar seminal plasma proteins and their aggregates present in the H+ and H- fractions with acid polysaccharides were estimated.
Keywords: Protein Binding; molekulová hmotnost; prasata; Heparin; tělesné tekutiny; Swine; proteiny; Body Fluids; Proteins; Male; makromolekulární látky; Hyaluronic Acid; Sperm Capacitation; Molecular Weight; vysokoúčinná kapalinová chromatografie; sekvenční analýza proteinů; mužské pohlaví; zona pellucida; polysacharidy; Chondroitin Sulfates; Chromatography, High Pressure Liquid; sperma; chromatografie afinitní; vazba proteinů; Semen; Animals; Dextran Sulfate; kapacitace spermií; Sequence Analysis, Protein; zvířata; Zona Pellucida; Polysaccharides; Macromolecular Substances; chondroitinsulfáty; heparin; Chromatography, Affinity; kyselina hyaluronová; síran dextranu